Development of 3D animated video first responder life support (Choking) for baby safety - Ali, Azita; Yazid, Siti Fatimah (2021)
The project aims to design and develop 3D animated video First Responder Life Support (Choking) for baby safety. The development of this 3D animated video can help parents to understand and learn more clearly about Basic Life Support in dealing with the issue of baby choking. High risk occurs in unregistered care centers because they do not have the knowledge or equipment available in the event of an accident with the baby (Rozmi, 2002). One of the main causes of choking is due to the careless attitude of the parent when giving the baby milk and the wrong position of the baby during breastfeeding. The model used in the development of this product is the Hannafin and Peck which has three main phases namely need assessment, design and develop or implement. Each phase will go through to the evaluation and revision. The analysis phase was conducted through interviews to find out the problem. This design phase of the product, the developer creates a storyboard and gets feedback from interface and design specialists. In the development or implementation phase, the developer creates a prototype using selected hardware and software. The evaluation is carried out by two (2) specialists in a creative multimedia field from the Faculty of Technical and Vocational Education (FPTV), while one (1) content specialist who teaches the course of First Responder Life Support (Choking) for baby in civil defense. The instrument of study used is the expert checklist form. Data is analyzed using frequency and percentage method. The findings of the study found that as a whole three specialists gave a positive response to this product. The results obtained by this product can help parents to learn Basic Life Support for baby choking.